Assessment of Antibiotic-Resistant Bacteria in Recreational Coastal Waters of Çanakkale, Türkiye - Belgin Kılıç Çetinkaya; Mine Çardak (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries)
This study investigates the prevalence of antibiotic-resistant bacteria in recreational coastal waters along the Çanakkale Strait (Türkiye), a region experiencing increasing anthropogenic pressure from urbanization, maritime activity, and seasonal tourism. A total of 211 bacterial isolates were obtained from surface seawater samples collected at 14 different recreational coastal sites during the summer season of 2024. These isolates were identified using the VITEK® 2 Compact system and tested against 15 antibiotics via the Kirby-Bauer disk diffusion method, following CLSI (2018) guidelines. The results revealed alarmingly high resistance rates, with vancomycin (92.89%), kanamycin (81.04%), and sulphonamides (64.45%) being the most affected. The Multiple Antibiotic Resistance (MAR) index ranged from 0.14 to 0.71, with over 95% of isolates scoring ≥ 0.2, indicating exposure to high-risk environments. Escherichia coli, Enterococcus faecalis, Staphylococcus intermedius and Bacillus cereus were among the most frequently isolated multidrug-resistant species. Comparative analysis with other marine studies from Türkiye confirms that Çanakkale’s coastal waters are significantly impacted by antibiotic contamination. The findings highlight the urgent need for regular surveillance and enhanced wastewater treatment strategies to mitigate the spread of resistance genes in coastal ecosystems. This study contributes essential baseline data to the national inventory on marine antibiotic resistance and underscores the public health risks posed by recreational waterborne exposure to resistant bacteria.